Platelets and Cardiac Arrhythmia - De Jong, Jonas S.; Dekker, Lukas R. (Frontiers in Physiology, 2010)
Sudden cardiac death remains one of the most prevalent modes of death in industrialized countries, and myocardial ischemia due to thrombotic coronary occlusion is its primary cause. The role of platelets in the occurrence of SCD extends beyond coronary flow impairment by clot formation. Here we review the substances released by platelets during clot formation and their arrhythmic properties. Platelet products are released from three types of platelet granules: dense core granules, alpha-granules, and platelet lysosomes. The physiologic properties of dense granule products are of special interest as a potential source of arrhythmic substances. They are released readily upon activation and contain high concentrations of serotonin, histamine, purines, pyrimidines, and ions such as calcium and magnesium. Potential arrhythmic mechanisms of these substances, e.g. serotonin and high energy phosphates, include induction of coronary constriction, calcium overloading, and induction of delayed after-depolarizations. Alpha-granules produce thromboxanes and other arachidonic acid products with many potential arrhythmic effects mediated by interference with cardiac sodium, calcium and potassium channels. Alpha-granules also contain hundreds of proteins that could potentially serve as ligands to receptors on cardiomyocytes. Lysosomal products probably do not have an important arrhythmic effect. Platelet products and ischemia can induce coronary permeability, thereby enhancing interaction with surrounding cardiomyocytes. Antiplatelet therapy is known to improve survival after myocardial infarction. Although an important part of this effect results from prevention of coronary clot formation, there is evidence to suggest that antiplatelet therapy also induces anti-arrhythmic effects during ischemia by preventing the release of platelet activation products.